Proses Pembelajaran Vokal dengan Memanfaatkan TikTok sebagai Sumber Belajar Digital - Erika Amelia; Riyan Hidayatullah (Universitas Negeri Medan, 2026)
This study aims to describe the vocal learning process using TikTok as a digital learning resource, analyze its benefits in improving students' skills and motivation, and identify obstacles encountered in its implementation. Methods: This study used content analysis of 30 viral TikTok audio and videos in 2025–2026 to understand the relationship between vocal learning, digital learning resources, the learning process, and TikTok. Results and Discussion: The research findings indicate that TikTok can be an effective digital learning resource for vocal learning because it provides clear practice models, improves students' skills and motivation through interactive features, and allows flexible learning anywhere. Conclusion: TikTok can be used as an effective and innovative vocal learning medium, because it can improve students' skills, motivation, and learning flexibility.